INOVASI RUMAH VERTIKAL KEPITING BAKAU (RVKB) BAGI KELOMPOK BUDIDAYA NELAYAN KAMPUNG LETTE, MAKASSAR - Hamrun, Hamrun; Amalia, Andi Annisa; Wahyu, Farhanah (Universitas Padjadjaran, 2026)
The community service program themed